PERJANJIAN KERJA BERSAMA ANTARA PEKERJA DAN PENGUSAHA - MH, Asuan; Dedeng, Dedeng (Solusi, 2025)
The research discusse The discussion in this research is about the formation of collective work agreements and the function of agreements in employment relations according to Law no. 13 of 2003 concerning Employment. Type of normative legal research with a legal approach related to the issues discussed with the conclusion that a collective work agreement is formed in a company, an agreement formed by workers (labor unions) and employers whose contents contain regulations or rights and obligations in the employment relationship which is recognized by the government as the labor relations supervisory body (Department of Manpower and Transmigration) is regulated in Law no. 13 of 2003 concerning Employment Article 1 number 24 and Article 124 paragraphs 1, 2 and 3. The purpose and function of forming a collective work agreement based on the agreement between workers and employers is to protect the interests of workers and employers in work relations both inside and outside the company (Article 116 Labour Laws).